2012
DOI: 10.1063/1.4704126
|View full text |Cite
|
Sign up to set email alerts
|

Atomic imaging of atomic layer deposition oxide nucleation with trimethylaluminum on As-rich InGaAs(001) 2 × 4 vs Ga/In-rich InGaAs(001) 4 × 2

Abstract: Formation of a contaminant free, flat, electrically passive interface to a gate oxide such as a-Al(2)O(3) is the critical step in fabricating III-V metal oxide semiconductor field effect transistors; while the bulk oxide is amorphous, the interface may need to be ordered to prevent electrical defect formation. A two temperature in situ cleaning process is shown to produce a clean, flat group III or group V rich InGaAs surface. The dependence of initial surface reconstruction and dosing temperature of the seedi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
25
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 36 publications
(42 reference statements)
1
25
0
Order By: Relevance
“…dangling bond density over a wide temperature range from 25 C and 280 C. 13 These prior STM/STS results are consistent with our C-V result showing that the effect of TMA dosing on the interface defect density appears to be temperature independent.…”
Section: -2supporting
confidence: 90%
See 2 more Smart Citations
“…dangling bond density over a wide temperature range from 25 C and 280 C. 13 These prior STM/STS results are consistent with our C-V result showing that the effect of TMA dosing on the interface defect density appears to be temperature independent.…”
Section: -2supporting
confidence: 90%
“…Figure 1 plots multi-frequency C-V curves for the MOS capacitors fabricated on n-type and p-type InGaAs(100) surfaces which were decapped at 370 C (low-T decap) and 460 C (high-T decap) followed by the normal ALD-Al 2 O 3 procedure without any TMA pre-dosing. Based on previous studies of InGaAs(001) with As 2 decapping and annealing at similar temperatures to those used in this research, 13,14 it is believed that the InGaAs surfaces decapped at 370 C and 460 C in this research form predominantly As-rich 2 Â 4 surface reconstructions and In/Ga-rich 4 Â 2 surface reconstructions, respectively. From Figure 1, the high-T decapped n-InGaAs sample (In/Ga-rich surface) shows larger frequency dispersion over the gate bias range from À2 V to 0 V and larger C-V stretch-out than the low-T decapped n-InGaAs (As-rich surface) capacitor, which indicates a higher density of interface defects on the high-T decapped n-InGaAs.…”
mentioning
confidence: 53%
See 1 more Smart Citation
“…To reduce the large trap densities at interfaces between In 0.53 Ga 0.47 As and the gate dielectric (typically Al 2 O 3 or HfO 2 ), various surface preparation and passivation methods are currently being investigated. [1][2][3][4][5][6][7][8][9] Interface trap densities (D it ), at least around midgap, are relatively straight-forward to detect for In 0.53 Ga 0.47 As, because of its narrow band gap (0.75 eV (Ref. 10)); they cause, for example, a frequency-dependent hump in the depletion region of capacitance-voltage (CV) characteristics, 11,12 and peaks in normalized conductance maps.…”
Section: Introductionmentioning
confidence: 99%
“…Details of the (2 × 4) reconstruction are given elsewhere. 20,21 Samples were subsequently exposed to atomic H generated from an Oxford Applied Research TC-50 thermal gas cracker. The hydrogen doses are reported in Langmuir (1 L = 1 s at 1 × 10 −6 Torr) based on the H 2 pressure; however, the cracking efficiency is reported to be closer to 50% (Oxford Applied Research) but could not be verified; therefore, the reported atomic H doses are an upper limit.…”
Section: Methodsmentioning
confidence: 99%